Genome‐wide based model predicting recovery from portosystemic shunting after liver shunt attenuation in dogs. (17th May 2018) - Van den Bossche, Lindsay; van Steenbeek, Frank G.; Weber, Maarten F.; Spee, Bart; Penning, Louis C.; van Sluijs, Freek J.; Zomerdijk, Flin; Groot Koerkamp, Marian J. A.; Rothuizen, Jan; Burgener, Iwan A.; Kummeling, Anne
Abstract : Background: In dogs with congenital portosystemic shunt (CPSS), recovery after surgical CPSS attenuation is difficult to predict. Objectives: Our aim was to build a model with plasma albumin concentration and mRNA expression levels of hepatic gene products as predictors of recovery from portosystemic shunting after surgery. Animals: Seventy‐three client‐owned dogs referred for surgical attenuation of CPSS. Methods: A prediction model was constructed using 2 case‐control studies of recovered and nonrecovered dogs after surgical CPSS attenuation. In the 1st study, a dog‐specific gene expression microarray analysis was used to compare mRNA expression in intraoperatively collected liver tissue between 23 recovered and 23 nonrecovered dogs. In the 2nd study, preoperative plasma albumin concentration and the expression of microarray‐selected genes were confirmed by RT‐qPCR in intraoperatively collected liver samples of 31 recovered and 31 nonrecovered dogs, including 35 dogs from the 1st study. Results: In the 1st study, 43 genes were differently expressed in recovered and nonrecovered dogs. The mean preoperative plasma albumin concentration in recovered dogs was higher compared to nonrecovered dogs (23 and 19 g/L, respectively; P = .004). The best fitting prediction model in the 2nd study included preoperative plasma albumin concentration and intraoperative DHDH, ERLEC1, and LYSMD2 gene expression levels. Conclusion and Clinical Importance: A preclinical model was constructed using preoperative plasma albumin concentration and intraoperative hepatic mRNA expression of 3 genes that were unbiasedly selected from the genome to predict recovery from portosystemic shunting after shunt ligation. Further development is essential for clinical application.